The Impact of Incentives and Sanctions on Educators’ Performances - Lubis, Nasib Samsuri (Global Action and Education for Society, 2025)
This study aims to assess the impact of rewards and punishments on educators' performance. This study employs a quantitative methodology. The study's population comprised 40 respondents (teachers) from two schools, State Junior High Scholl (SMPN) 1 and 2 Rumbio Kampar. The data collection method employed in this study was a questionnaire utilizing a Likert scale ranging from 1 to 5. The analytical method employed was multiple linear regression analysis. The study's results indicated that reward provision influenced teacher performance, yielding a t count of 8.929 and a t table value of 2.021 (significance level 5%, n = 40). The imposition of penalty affects instructors' performance, yielding a t count of 5. The impact of reward and punishment provisions on educator performance at State Junior High Scholl (SMPN) 1 and 2 Rumbio Kampar is significantly 71.6%. The R Square value is 0.716. The reward and punishment system affects educator performance by 71.6%, while the remaining 28.4% is attributed to other variables in this study.